Pemahaman Bullying di Sekolah - Fitriyah, Fitriyah (Jurnal Ilmu Kesejahteraan Sosial, 2008)
This research was conducted to determine the understanding of the concept of bullying from the teachers, students and the perpetrator, the victim's parent and also the efforts to prevent bullying and the constraints to eliminate bullying in schools. This research was conducted with qualitative research approach and descriptive research with research sites in SMUN in South Jakarta. The survey results revealed that the school including teachers, perpetrators and victims of bullying and parents do not understand about bullying which is still a lot of bullying occurred at school However the school has sought to minimize with various efforts such as granting sanctions against perpetrators, although bullying often happens outside the school environment so that it is difficult to detect In addition there is a tendency also from the school to cover up the problem of school bullying because this is one leading school in South Jakarta district